Downregulated hsa_circ_0077837 and hsa_circ_0004826, facilitate bladder cancer progression and predict poor prognosis for bladder cancer patients. (6th April 2020) - Shen, Chong; Wu, Zhouliang; Wang, Yujie; Gao, Shen; Da, La; Xie, Linguo; Qie, Yunkai; Tian, Dawei; Hu, Hailong
Abstract: Growing evidence has indicated that circular RNAs (circRNAs) play crucial roles in multiple biological processes. However, alterations in circRNA profiles during bladder cancer progression and the clinical significance thereof remain unclear. Therefore, high‐throughput RNA sequencing was conducted to identify circRNA and mRNA profiles in five pairs of bladder cancer tissues and adjacent noncancerous tissues. A total of 87 differentially expressed circRNAs and 2756 mRNAs were detected in above bladder cancer samples compared with paired noncancerous samples. Functional enrichment analyses, circRNA‐microRNA‐mRNA, and protein‐protein interaction networks revealed that these dysregulated circRNAs were potentially involved in carcinogenesis and evolution of bladder cancer. Subsequently, the differential expression of eight circRNAs was detected by real‐time qPCR. Hsa_circ_0003141 and hsa_circ_0008039 were significantly upregulated as well as hsa_circ_0026782, hsa_circ_0077837, hsa_circ_0004826, and hsa_circ_0001946 were significantly downregulated among validation of 70 matched bladder cancer tissues (≥75%). Moreover, hsa_circ_0077837 and hsa_circ_0004826 were also verified as markedly downregulated in four bladder cancer cells (100%). Naturally, hsa_circ_0077837 and hsa_circ_0004826 were also demonstrated using RNase‐R+ resistance experiments. In addition, Fisherʹs exact test, Kaplan‐Meier plots, Cox regression analyses, and receiver operating characteristic curve was performed to assess their clinical value. Downregulation of hsa_circ_0077837 and hsa_circ_0004826 all was significantly correlated with worse clinicopathological features and poor prognosis of bladder cancer patients. The area under the receiver operating characteristic curve of them was 0.775 ( P  < .0001) and 0.790 ( P  < .0001), respectively. Not surprisingly, in vitro functional experiments also demonstrated that the overexpression of hsa_circ_0077837 and hsa_circ_0004826 significantly weakened the proliferation, migration, and invasion of bladder cancer cells. Overall, hsa_circ_0077837 and hsa_circ_0004826 might act as tumor suppressors in the bladder cancer progression and serve as a potential biomarker for the diagnosis, prognosis, and therapy of bladder cancer. Abstract : The transcriptional data of circRNAs and mRNAs were deeply detected by high‐throughput RNA sequencing and systematically analyzed using bioinformatics in patients with BC; and these eight dysregulated circRNAs were also verified by real‐time qRT‐PCR. Correlation analysis of clinicopathological features and survival analyses of circRNAs in BC were conducted. Functional experiments with circ_0077837 and circ_0004826 overexpression significantly weakened the progression of BC cells.